Merawat Diri, Mengenal Emosi: Membangun Emotional Well-Being (Psikoedukasi untuk Siswa SMA Providentia) - Juniarti, Fifi (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service program aims to strengthen the emotional well-being of 11th-grade students through education on contributing factors, the value of healthy social interactions, and strategies for developing self-regulation. The activity was delivered in the form of psychoeducation titled "Caring for Yourself, Knowing Your Emotions: Building Emotional well-being" at SMA Providentia, West Jakarta. The session involved lectures and reflective discussions, attended by 43 students. Evaluation responses from 20 participants showed positive feedback, with average scores of 3.41 out of 4 in aspects such as educational value, objectivity, accountability, and transparency. The program successfully introduced three key dimensions of emotional well-being: hedonia, eudaimonia, and evaluative well-being. It is expected that this understanding will support students in managing emotional challenges, particularly in their final year of school.